ANALISIS PENGAKUAN, PENGUKURAN, PENYAJIAN DAN PENGUKURAN ASET TETAP PADA PT PLASTICON TRIJAYA DAN KESESUAIANNYA DENGAN PSAK 16 - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2017)
The purposes of this study was to analyze the recognition, measurement, presentation, and disclosure of Fixed Assets as well as compliance with Statement in Indonesian Accounting Standard No. 16 in PT Plasticon Trijaya. This study is a qualitative study with descriptive analysis and comparison between the data obtained from the company with Statement in Indonesian Accounting Standard No. 16.  The results of this research is the treatment of fixed assets has been largely in accordance with SFAS 16, there is little error in presentation and disclosure of Fixed Assets in the Financial Statements.